CREATIVE THINKING ABILITY THROUGH FIELD TRIP LEARNING ON ECOSYSTEM MATERIAL - Nugraha, Septian; Adisendjaja, Yusuf Hilmi; Amprasto, Amprasto (Jurnal Pendidikan Biologi, 2017)
Teachers improve learning activity and creativity of students in ecosystem that is using a field trip. Students activities in a field trip are guided through a worksheet to facilitate their observation. Field trip activities implemented in place of Wahana Edukasi Global (WAGLO) Cisalak of Subang District, West Java Province. This study aims to identify and analyze creative thinking ability of students in carrying out field trip. The method used was weak experimental design with one group pretest-posttest. Population subjects in this study were students of grade 10th MA Al-Husna Cisalak Subang District West Java Province. The sample is determined by purposive sampling technique. Data collection was done through a test of creative thinking ability that given at the beginning and end of learning. Data was analyzed by calculating N-gain test result. The results showed that field trip provide enhanced creative thinking ability of students with index N-gain of 0.48 is included in the medium category.